Evaluating Motion Sickness Responses to the Virtual Horizon in VR-HMDs: A Real-World Marine Study - Wardani, Kartika Kusuma; Artana, Ketut Buda; Zulaikha, Ellya; Semin, .; Dinariyana, Anak Agung Bagus; Pratiwi, Emmy (Engineering, Technology & Applied Science Research, 2025)
Motion sickness continues to be a significant issue for ferry passengers, especially in fluctuating marine conditions, where immediate visual stability is absent. Despite the growing utilization of Virtual Reality (VR) systems, there is a limited understanding of the ideal visual configurations to alleviate Visually Induced Motion Sickness (VIMS) in maritime environments. This study examines how varying the horizon-deviation angles shown through a VR Head-Mounted Display (VR-HMD) affects the intensity of motion sickness during real boat trips. During a three-day field test, 15 participants encountered five virtual horizon deviations (0–25°) while experiencing pitching and rolling motions on a Lembar–Padang Bai ferry. The responses on the Simulator Sickness Questionnaire (SSQ) satisfied the assumptions for linear regression, indicating that each 1° deviation increased the SSQ ratings by 1.311 points (p = 0.002), while the moderate sea states contributed an additional 23.281 points (p = 0.030). The Motion Illness Symptom Classification (MISC) scale identified symptom exacerbation only at 20 to 25° (H = 13.14; p = 0.011). The substantial SSQ–MISC correlation (ρ = 0.818) validates the reliability of both instruments. The resultant prediction model provides an inaugural field-based guideline for enhancing virtual horizon configurations in adaptive VR designs for marine applications.